Pengaruh Price Discount dan E-service Quality terhadap Perceived Value: Studi pada Pengguna Shopeefood di Kalangan Generasi Z Yogyakarta - Ilvano Iswandi; Andriya Risdwiyanto; Bambang Irjanto (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2025)
This study aims to determine the effect of price discount (X1) and e-service quality (X2) on perceived value (Y) among Generation Z ShopeeFood users in Yogyakarta. This study used a quantitative approach with a sample of 60 Generation Z respondents aged 17-28 who had made a transaction on ShopeeFood in the past three months. Data were collected through an online questionnaire and analyzed using Structural Equation Modeling (SEM) with SmartPLS 4.0. The results of this study indicate that price discount has a positive and highly significant effect on perceived value, as evidenced by a strong path coefficient and a high t-statistic. E-service quality was also found to have a positive and significant effect on perceived value. Thus, both variables simultaneously significantly and strongly explain variation in perceived value, with the model demonstrating a good fit to the data. This study confirms that price discount strategies are a key driver in shaping perceived value among Generation Z consumers, and e-service quality also plays a crucial role in creating positive digital experiences. The practical implications of this study include recommendations for ShopeeFood managers to optimize discount strategies and continuously improve e-service quality to enhance consumer perceived value.